Scuba diving death: Always due to drowning? Two forensic cases and a review of the literature. (March 2018) - Aquila, I; Pepe, F; Manno, M; Frati, P; Gratteri, S; Fineschi, V; Ricci, P
Scuba diving is an increasingly common recreational activity. We describe the physiopathology of barotrauma in two cases where death was caused by pulmonary barotrauma while diving. An inspection and autopsy were carried out in both cases. The autopsy data were supported by post-mortem radiological investigation. Histological and toxicological analyses were also carried out, and dive computer and tank manometer analysis performed. In both cases, the cause of death was attributable to arterial gas embolism, resulting from pulmonary barotrauma subsequent to pulmonary over-distension. The dive computer analysis and the tank manometer allowed us to understand what happened underwater. In our opinion, a multidisciplinary approach is crucial in order to clarify the cause of death. Some pathological conditions and risk factors should be considered before diving.